Tornando-se sujeito da sua história de aprendiz de língua inglesa: uma experiência com sequências didáticas na EJA - Aguiar, Claudiane Costa (2012)
This study is situated in the field of Applied Linguistics and aims at investigating the impacts of the use of a Didactic Sequence as an alternative for the teaching of the English language with a group of EJA students at a public school in João Pessoa. The theoretical framework is based on the studies developed by Dolz, Noverraz e Schneuwly (2004) who assert that introducing students to language practices by means of the use of text genres is a primary role of the school. Their work is based on the Sociodiscursive Interactionism approach (BRONCKART, 1999; 2006; 2008), a socio-communicative perspective of language which conceives it as action and whose expansion in Brazil has occurred due to the studies carried out by names as those of Cristovão (2001, 2005, 2007, 2008, 2009), Machado and Guimarães (2009), Pereira R. (2009), Medrado (2010), among others. The specific objectives are making up and giving progression activities to work with the genre personal profile in the English language subject; analyzing the text productions by the students, observing the development of their language capacities; discussing the didactic validity of the progression activities with EJA; besides presenting a brief analysis of the impact of the use of DSs in the teaching practice of the participant teacher of this research. This assumes that the lack of sequenced material exacerbates the problem of the English language teaching with EJA. The corpus was collected in one of the Public Municipal Schools in João Pessoa city through field notes. The results demonstrate that the students had difficulties to make use of language capacities while producing their texts in both, mother tongue and in English, revealing that they lacked previous work targeted at literacy in initial cycles. Despite these obstacles, the results indicate that the use of DSs with EJA group in the English language is feasible and this proposal can be used to turn the process of teaching and learning languages with EJA groups dynamic.